As propostas educacionais da administração de Luiz Alves de Lima e Silva (Duque de Caxias): um estudo da instrução Rio-grandense do século XIX (1842-1871) - Valle, Hardalla Santos do (2013)
Between 1842 and 1846, Luiz Alves de Lima e Silva (Duque de Caxias) was Commander in Chief of the Army Operations and President of the Province of St. Peter of Rio Grande do Sul. From this, the present study aims to argue about trajectory of political and administrative by Caxias, and specifically about their actions and proposals during this educational experience. In the quest for understanding the dimensions attained by these educational proposals, also traveled provincial administrations followed by Caxias, in the year 1871 when the Liceu D. Afonso, one of his proposals, after 20 years of operation, is closed. In this perspective, we present the following guiding questions of this paper: Why Luiz Alves de Lima e Silva developed these educational proposals? What were these proposals? They came to take effect? The sources used in this study are: official documents, such as bylaws, agendas, minutes and crafts, as well as reports of travelers and newspapers. The method chosen was the document analysis, understood as a set of research techniques whose aim is to search for the meaning or meanings of a written document. Among the results, we highlight the perception of the role it could play a strong and organized education in the province of San Pedro. This was fully understood by Caxias, so getting the support of the population, and avoiding as much as possible that new riots and / or rebellions started. Thus, the educational reforms of the ways found by Luiz Alves de Lima e Silva to achieve this. Given the above with, this dissertation we aim to foster attention and reflection, through the prism of Cultural History, about the performance of Caxias regarding the instruction of the Province of São Pedro do Rio Grande do Sul A story characterized by interests, disputes, political and strong subjects, as Luiz Alves de Lima e Silva. Therefore, this study aggregator, both the novelty of the subject matter, as the chosen approach, capable of contributing, through new insights, the History of Education Rio-Grandense nineteenth century.